PENILAIAN OBYEK DAYA TARIK WISATA ALAM PULAU SEPANDAN TAMAN NASIONAL BETUNG KERIHUN DAN DANAU SENTARUM KALIMANTAN BARAT - Rifanjani, Slamet; Sahmantha, Oudilla Gressa; Ardian, Hafiz (Universitas Tanjungpura, 2024)
Sepandan Island has a diversity of flora and fauna, uniqueness and natural beauty which has the potential to be attractive as a tourist attraction. Sepandan Island is located in the middle of Lake Sentarum in the Betung Kerihun and Lake Sentarum National Park area. This area is visited by many people, especially on holidays, to enjoy the beauty and uniqueness of Sepandan Island. Assessment of the natural tourist attractions of Sepandan Island is needed for planning the development of tourist areas. The aim of this research is to assess the potential of Sepandan Island's natural tourist attractions and classify its development elements into categories of potential, moderate potential or not potential for development. The method used is a survey method in the form of a questionnaire to collect information regarding potential tourist attractions. Determining respondents used the purposive sampling method according to the specified criteria. The results of research into the classification of the Sepandan Island ODTWA from the criteria for assessing tourist attraction, accessibility, socio-economic conditions, accommodation, supporting facilities and infrastructure, and availability of clean water obtained a total score of 3522.8 and the classification for assessing the potential of its elements is classified as potential for development.Keyword: Attraction, Natural tourism, Sepandan island.AbstrakPulau Sepandan memiliki keanekaragaman flora dan fauna, keunikan serta keindahan alam yang mempunyai potensi daya tarik sebagai obyek wisata. Pulau Sepandan terletak di tengah danau Sentarum di kawasan Taman Nasional Betung Kerihun dan Danau Sentarum. Kawasan ini banyak dikunjungi oleh masyarakat terutama pada hari libur untuk dapat menikmati keindahan dan keunikan Pulau Sepandan. Penilaian objek daya tarik wisata alam Pulau Sepandan diperlukan untuk perencanaan pengembangan kawasan wisata. Tujuan dari penelitian ini adalah untuk menilai potensi obyek daya tarik wisata alam Pulau Sepandan dan mengklasifikasi unsur pengembangannya ke dalam katagori potensial, cukup potensial atau tidak potensial dikembangkan. Metode yang digunakan adalah metode survei dalam bentuk kuesioner untuk mengumpulkan informasi mengenai potensi daya tarik wisata. Penentuan responden menggunakan metode purposive sampling sesuai dengan kriteria yang ditentukan. Hasil penelitian klasifikasi ODTWA Pulau Sepandan dari kriteria penilaian daya tarik wisata, aksesibilitas, kondisi sosial ekonomi, akomodasi, sarana dan prasarana penunjang, dan ketersediaan air bersih mendapatkan nilai total sebesar 3522,8 dan klasifikasi penilaian potensi unsur nya adalah tergolong potensial dikembangkan.Kata kunci: Daya tarik, Pulau Sepandan, Wisata alam.